Orderly Eats: AI Enabled Smart Ordering and Canteen Service (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid growth of the demand for quick and easy services in schools and universities brought about the transferring of the traditional canteen operations to virtual means. The article presents orderly eats, a food ordering application, which has been developed in order to facilitate students in their canteen ordering. The app lets students check the menu, place orders at any spot, and enter a little info such as their name and faculty and pay via a secure UPI QR code-based payment system. Once a payment is completed, the app creates a specific order token. This allows students to avoid the long queues and collect their food when it is comfortable for them. The backend consists of Firebase Firestore for real-time database and order tracking, while the Android interface is built with Java using Android Studio. The canteen personnel is equipped with an admin interface that gets new orders, manually verifies payments, and changes order statuses such as Approved and Ready for Pickup. These changes are immediately shown in the student's app, which guarantees efficient communication. The system that has been presented increases the operational efficiency, lowers the waiting time, decreases the number of people at the canteen during peak hours, and improves the user's overall experience. The app was built as a mini-project that demonstrates the practical uses of mobile development, cloud database integration, and digital payment processes. It has been shown that Namma Canteen can not only modernize the management of the canteen to a great extent but also provide a solid ground for the future improvements such as automatic payment verification and push notifications.